Building functional connectivity neuromarkers of behavioral self-regulation across children with and without Autism Spectrum Disorder. (February 2020) - Rohr, Christiane S.; Kamal, Shanty; Bray, Signe
Abstract: Behavioral self-regulation develops rapidly during childhood and struggles in this area can have lifelong negative outcomes. Challenges with self-regulation are common to several neurodevelopmental conditions, including Autism Spectrum Disorder (ASD). Little is known about the neural expression of behavioral regulation in children with and without neurodevelopmental conditions. We examined whole-brain brain functional correlations (FC) and behavioral regulation through connectome predictive modelling (CPM). CPM is a data-driven protocol for developing predictive models of brain–behavior relationships and assessing their potential as 'neuromarkers' using cross-validation. The data stems from the ABIDE II and comprises 276 children with and without ASD (8–13 years). We identified networks whose FC predicted individual differences in behavioral regulation. These network models predicted novel individuals' inhibition and shifting from FC data in both a leave-one-out, and split halves, cross-validation. We observed commonalities and differences, with inhibition relying on more posterior networks, shifting relying on more anterior networks, and both involving regions of the DMN. Our findings substantially add to our knowledge on the neural expressions of inhibition and shifting across children with and without a neurodevelopmental condition. Given the numerous behavioral issues that can be quantified dimensionally, refinement of whole-brain neuromarker techniques may prove useful in the future.